Effects of Na2O on optical and radiation shielding properties of xNa2O-(20-x)K2O-30V2O5-50TeO2 mixed alkali glasses - Mohd Azlan Nafiah (Tanjung Malim, 2021)
Effects of Na2O on optical and radiation shielding properties of xNa2O-(20-x)K2O-30V2O5-50TeO2 mixed alkali glasses by Mohd Azlan Nafiah